Photoresponsive Materials: Photoresponsive Cucurbit[8]uril‐Mediated Adhesion of Bacteria on Supported Lipid Bilayers (Small 46/2015). Issue 46 (7th December 2015) - Sankaran, Shrikrishnan; van Weerd, Jasper; Voskuhl, Jens; Karperien, Marcel; Jonkheijm, Pascal
Abstract : Inspired by nature's ability to capture and release biological entities when required, P. Jonkheijm and co‐workers have developed a microfluidic platform for the adhesion and light‐triggered release of pathogenic E. coli. On page 6187, they achieve this using supported lipid bilayers bearing a ternary complex of methylviologen, a supramolecular host (cucurbit[8]uril), and a photo‐active azobenzene glycoconjugate. The platform has the potential to be used for intricate fundamental studies dealing with the spatio‐temporal characteristics of celladhesion and also the development of novel reusable biosensors.